The Influence of Work Discipline on Employee Health and Safety in the Era of the Covid-19 Pandemic - Srimulatsih, Mahbubah (International Journal of Management and Business Applied, 2022)
The purpose of this study was to determine the effect of work discipline on occupational health and safety. The research was conducted in a private company in Riau Province. This research is a quantitative research using SPSS version 25 to test hypotheses and data processing.The results of the analysis found that work discipline had a positive and significant effect on the Occupational Safety and Health of Employees. Based on the determinant test, the value of R square is obtained at 0.594 or 59.4%, which means that work discipline has an influence on Occupational Health and Safety.Employeethe remaining 40.6% is influenced by other variables not examined in this study.